(untitled) (Fiep Bulletin - online, 2014)
The following paper has as its pivotal goal to assess the Quality of Life (QOL) Indicators of College Students. The WHOQOL - 100 model was used as a data collecting tool, through the probabilistic demonstration per conglomerate with n = 130. The QOL indicators showed the following domains, with enhanced and worst evaluation: Independence Level (78.82%) and Physical (58.83%); the following aspects as better and worst facets: Dependence on Medicinal substances and Medical aids (12.80%) and Physical Safety and Security (48.05%); setting high quality level of QOL from those evaluated (78.4%). It was concluded that the average QOL could be classified as good, with scope for improvement reaching up to 31.69%.